Pan-cancer analysis of homologous recombination deficiency and homologous recombination repair–associated gene alterations in solid tumors from a large Asian cohort - Lili Ren; Runsi Yao; Ting Hou; Chenglin Liu; Fei Zhao; Xiaojun Chen; Zhou Zhang; Yan Huang (BMC Cancer)
Abstract Background Homologous recombination deficiency (HRD) is associated with sensitivity to platinum-based chemotherapy and PARP inhibitors in BRCA-associated cancers, including ovarian, breast, prostate, and pancreatic cancers. This study explores HRD and homologous recombination repair (HRR) gene alterations in a pan-cancer cohort to guide precision oncology. Methods Clinical and genomic data from 9,262 patients with 17 solid tumor types were analyzed using the OncoScreenTM Plus kit. HRD scores, biallelic HRR and tumor suppressor gene alterations, and their clinical correlations were evaluated. Results HRD scores varied across cancer types, all showing a long tail in distribution. The prevalence of pathogenic alterations in pan-cancer HRR was 21.3%, with 13.7% of the cases having an HRD score ≥42. HRD-related events (LOH, LST, and TAI) exhibited similarities and cancer-specific patterns at the chromosomal arm level. Biallelic loss of HRR genes, especially BRCA1, BRCA2, RAD51D, RAD51 C, and PPP2R2 A was linked to higher HRD scores in BRCA-associated cancers, while BARD1, RAD51D, RAD54L, BRCA1, and MRE11 were associated with elevated HRD scores in in other cancer types (non-BRCA cancers). TP53 biallelic alterations, with or without HRR alterations, were linked to increased HRD scores. Higher HRD scores were associated with late-stage, older, metastatic, PD-L1 positive, non-MSI-H/non-POLE samples were correlated with genomic instability indexes, such as structural chromosomal instability (SCIN), weighted genome instability index (WGII), and whole-genome doubling (WGD). Conclusions This is the largest pan-cancer HRD study in an Asian population, providing insights for future HRD testing and targeted therapy.